The serotonin receptor 7 and the structural plasticity of brain circuits - Volpicelli, Floriana; Speranza, Luisa; di Porzio, Umberto; Crispino, Marianna; Perrone-Capano, Carla (Frontiers in Behavioral Neuroscience, 2014)
Serotonin (5-hydroxytryptamine, 5-HT) modulates numerous physiological processes in the nervous system. Together with its function as neurotrasmitter, 5-HT regulates neurite outgrowth, dendritic spine shape and density, growth cone motility and synapse formation during development. In the mammalian brain 5-HT innervation is virtually ubiquitous and the diversity and specificity of its signaling and function arise from at least 20 different receptors, grouped in 7 classes. Here we will focus on the role 5-HT7 receptor (5-HT7R) in the correct establishment of neuronal cytoarchitecture during development, as also suggested by its involvement in several neurodevelopmental disorders. The emerging picture shows that this receptor is a key player contributing not only to shape brain networks during development but also to remodel neuronal wiring in the mature brain, thus controlling cognitive and emotional responses. The activation of 5-HT7R might be one of the mechanisms underlying the ability of the CNS to respond to different stimuli by modulation of its circuit configuration.